Development and testing of a new pedagogical model in beginner-level solfège education - Kendüzler, Mustafa; Akkaş, Salih (Frontiers in Education, 2025)
Accurate vocal use and intonation skills are fundamental components of beginner-level solfège education. This pilot study aimed to develop and test a new pedagogical model designed to enhance beginner-level students’ vocal use and intonation skills in solfège performance. The model, developed specifically for this study, is referred to as the Vocal Use-Based Solfège Teaching Model. This study employed a true experimental pretest-posttest control group design. The pilot study involved a small sample of 12 beginner-level solfège students voluntarily recruited from Ankara Private La Vita Music Academy and randomly assigned to either the experimental or control group. Both groups completed a pretest using excerpts from solfège 1 textbook and were assessed with the Musical Reading Performance Test. During a six-week intervention period, the experimental group engaged in the newly designed solfège exercises, while the control group followed traditional curriculum materials. The pretest scores do not show a statistically significant difference between the experimental and control groups (p > 0.05). The posttest scores, however, indicate a statistically significant improvements in the experimental group, with a moderate effect size (Cohen’s d = 0.29). The findings demonstrate that the Vocal Use-Based Solfège Teaching Model offers a replicable and more effective approach to beginner-level solfège education compared to traditional methods.